2005
DOI: 10.1152/ajplung.00246.2004
|View full text |Cite
|
Sign up to set email alerts
|

Syk tyrosine kinase participates in β1-integrin signaling and inflammatory responses in airway epithelial cells

Abstract: The protein tyrosine kinase Syk is critically involved in immunoreceptor signaling in hematopoietic cells. Recent studies demonstrate Syk expression in nonhematopoietic cells, including fibroblasts, endothelial cells, hepatocytes, and breast epithelium. However, the role of Syk in these cells is uncertain. We hypothesized that Syk is expressed in respiratory epithelial cells (EC) and that it functions as a signaling molecule involved in inflammatory responses in the epithelium. With the use of immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
84
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 55 publications
9
84
2
Order By: Relevance
“…These results indicate that the redistribution of SYK was induced by the engagement of b1-integrins by fibronectin. Although SYK phosphorylation on Tyr525/526 has been demonstrated to be also induced by stimulation with fibronectin in airway epithelial cells, 13 we could not find induction of SYK phosphorylation at Tyr525/526 after adhesion of HCC cells to fibronectin (Supplementary Figure 6). Other tyrosine sites might be activated by stimulation with fibronectin in HCC cells.…”
Section: Redistribution Of Syk Following Adhesion To Fibronectincontrasting
confidence: 59%
See 3 more Smart Citations
“…These results indicate that the redistribution of SYK was induced by the engagement of b1-integrins by fibronectin. Although SYK phosphorylation on Tyr525/526 has been demonstrated to be also induced by stimulation with fibronectin in airway epithelial cells, 13 we could not find induction of SYK phosphorylation at Tyr525/526 after adhesion of HCC cells to fibronectin (Supplementary Figure 6). Other tyrosine sites might be activated by stimulation with fibronectin in HCC cells.…”
Section: Redistribution Of Syk Following Adhesion To Fibronectincontrasting
confidence: 59%
“…13 To identify whether the localization of SYK was altered in HCC cells due to the engagement of b1-integrins with fibronectin, SYK-tGFPtransfected Hep3B and Huh7 cells were plated on fibronectin-coated surfaces and subsequently examined by confocal microscopy. After 1 h, the adhesion to fibronectin induced visible cytoplasmic spreading of both Hep3B and Huh7 cells on coverslips.…”
Section: Redistribution Of Syk Following Adhesion To Fibronectinmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence demonstrated that it is also expressed by many non-hematopoietic cell types (Hoeler et a1., 2005;Ulanova et a1., 2005) and that it plays a negative role in cancer (Hoellenriegel et al, 2012). A significant drop in its expression was first observed during breast cancer progression, but an anomalous Syk expression has now also been evidenced in many other tumor types.…”
Section: Discussionmentioning
confidence: 99%